Pengaruh Fee Audit, Audit Tenure, Spesialisasi Auditor, Dan Ukuran Perusahaan Terhadap Kualitas Audit - Afyfah Putri Ramadya; Murtanto Murtanto; Hasnawati Hasnawati (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
This study aims to determine the effect of audit fee, audit tenure, auditor specialization, and size firm on audit quality in companies listed the Kompas 100 index on Bursa Efek Indonesia in 2020-2022 either partially or simultaneously. The type of data in this study is quantitative with secondary data. The sample used in this study was 76 companies with 228 financial statements. The sampling technique uses purposive sampling technique. The analysis methods used in this study are logistic linear regression analysis and descriptive analysis. The results showed that audit fee has a positive effect on audit quality, audit tenure has a negative effect on audit quality, while auditor specialization did not has negative effect on audit quality, and size firm did not has negative effect on audit quality.